2015
DOI: 10.1177/1057083715577696
|View full text |Cite
|
Sign up to set email alerts
|

Are They Ready to Teach With Technology? An Investigation of Technology Instruction in Music Teacher Education Programs

Abstract: The purpose of this research was to investigate the type, quantity, and effects of technology instruction currently being provided to undergraduate music education majors. Undergraduate participants ( n = 46) at 10 degree-granting institutions completed an online survey on the technology instruction received during their undergraduate degree programs and their plans for future technology implementation in their classrooms. Participants’ responses indicated that 63% had taken a required technology course during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 17 publications
1
17
0
4
Order By: Relevance
“…Rather, more than half of both studio and K-12 teachers felt their degrees did not at all prepare them with financial and business management skills or entrepreneurial skills, and a substantial percentage of the teachers felt that their institutions prepared them very little or not at all in terms of technological skills. This is consistent with previous research findings that have highlighted a perceived lack of budgeting skills (Ballantyne & Packer, 2004) and technological competence (Haning, 2016) among K-12 teachers. With 15.2% of studio teachers in this sample earning $10,000 or less per year and only 13.9% earning more than $30,000 per year, it would seem these skills are essential for studio teachers in particular.…”
Section: Discussionsupporting
confidence: 93%
“…Rather, more than half of both studio and K-12 teachers felt their degrees did not at all prepare them with financial and business management skills or entrepreneurial skills, and a substantial percentage of the teachers felt that their institutions prepared them very little or not at all in terms of technological skills. This is consistent with previous research findings that have highlighted a perceived lack of budgeting skills (Ballantyne & Packer, 2004) and technological competence (Haning, 2016) among K-12 teachers. With 15.2% of studio teachers in this sample earning $10,000 or less per year and only 13.9% earning more than $30,000 per year, it would seem these skills are essential for studio teachers in particular.…”
Section: Discussionsupporting
confidence: 93%
“…Participants rated their knowledge in technology-related domains lowest and indicated that personal exploration was one of their primary resources for learning in these areas. Similarly, Haning (2016) surveyed undergraduate preservice teachers about technology instruction and plans for technology implementation. Haning reported that most students had taken a technology-focused course and desired further training in technology integration.…”
Section: The Myth Of Generational Labelsmentioning
confidence: 99%
“…Much of the social media-based research in music education has focused on digital tools and their application (Albert, 2015;Nart, 2016;Williams, 2014), teacher preparation (Haning, 2016;Nart, 2016), potential impacts on learning (Portowitz et al, 2014;Webster, 2016), and education in the postdigital age (Clements, 2018). This research has increased our knowledge about the intersection of social media and music education in K-12 schools and institutions of higher learning.…”
Section: Review Of Literaturementioning
confidence: 99%